SISTEM PENDATAAN PENJUALAN PADA CV TASYA BUNGSU BERBASIS WEB - Kardoni Gulo; Solihin Solihin; Riska Hayati; Holilah Holilah (LPPM Unbaja, 2025)
In today's era, information technology is developing rapidly and is still growing, so that it demands everyone to keep abreast of technological developments by applying technology to all fields, including in the business sector. Sales data is very important to input and store properly for later management in order to be able to create invoices and delivery orders as well as generate sales data reports. On CV. Tasya Bungsu sales data collection process is still simple so there are still many obstacles in the implementation of the process and it is more time consuming so that the process is still less effective and efficient. So, there is a need for a more computerized sales data collection system, namely a web-based system that allows data collection to be more flexible anytime and anywhere without depending on one device. This study aims to identify and analyze the constraints faced by the object of research so that the authors can develop a web-based sales data collection system on CV. Tasya Bungsu to help overcome existing obstacles and assist the sales data collection process. The research method used in this study is a qualitative research method with a system development method, namely the RAD method. The process of developing the system and writing program code lines uses the PHP programming language and MySQL database with system design modeling using UML modeling. From the results and conclusions of this study, a sales data collection system was obtained that was able to assist the sales data collection process on CV. Tasya Bungsu became more effective and efficient